Provincial patriot of the French Revolution : François Buzot, 1760-1794 - Oliver, Bette Wyn, 1933- (Lexington Books, 2015)
Provincial Patriot of the French Revolution: François Buzot, 1760-1794, provides a personal perspective on the dramatic events of the French Revolution between 1789 and 1794. By examining the life and observations of this Girondin deputy from Evreux, it is possible to better understand the inherent difficulties involved in transforming an ancient monarchy into a modern republic.